(untitled) (Bulletin KNOB, 1998)
Johannes De Laet was a Leiden merchant and one of the directors of the Dutch West India Company. He also moved in the learned circles of Leiden University and was a good friend and assistant of professor Claude Saumaise. Apart from his business activities De Laet was also successful as a compiler of geographical descriptions and some works on the ancient classics. In 1649 the first complete edition of Vitruvius was published in Holland by the Amsterdam publisher Louis Elzevier, arranged by Johannes De Laet, M. Vitruvii Pollionis De Architectura Libri Decem. In this publication the treatise was accompanied by innumerable footnotes and all sorts of handwritings from Antiquity, from the Italian Renaissance and from contemporary Holland, in explanation of various aspects in the work of Vitruvius. The whole publication was in Latin, even the supplementary syllabus, and thus De Laet’s edition became the pre-eminent Vitrivius edition for later use. De Laet’s strength lay in collecting all the available, frequently scattered material on his subject. He presents it in a clear structure, but he does not formulate any theory or views of his own. In stead, he quotes amply from other works. The famous Vitruvius commentary of Guillaume Philander (1544) has been included almost in full in the footnotes, next to remarks by Daniele Barbaro from the latter’s Vitruvius commentary (1556) and by contemporaries such as Vossius and Claude Saumaise. In line with Philander, De Laet did not so much look for direct applicabilities of the rules of Vitruvius, but rather for an understanding of Antiquity itself, from a scientific interest in the mathematical-philosophical foundations of classical architecture and art. Consequently, as a supplement to Vitruvius, De Laet provides writings which pursue this subject in particular, starting with the measurements and weights in Antiquity itself (Agricola 1551) and followed by the musical harmony principles (Meibomius 1649) and the mathematical rules in painting and sculpture (among others, Alberti’s De Pictura.) In that sense Henry Wotton’s The Elements of Architecture (1624) was an excellent choice as an introduction to this entire compilation of classical and more contemporary treatises. De Laet’s work shows many resemblances with earlier attempts by Constantijn Huygens in 1642 to have Vitruvius translated into Dutch. Wotton’s Elements had been intended as an introduction to Vitruvius himself in this project, which the architect Jacob van Campen would also participate in. Other aspects of De Laet’s edition, too, coincide with Huygens’s plan, such as the stress on the coherence between musical harmony and the architectural proportion theory. Possibly Huygens gave advice from a distance through Saumaise, who was a friend of his, after his own Vitruvius edition had been called off. However, there is no concrete evidence for Huygens’s direct involvement in the edition of 1649.